Knot staining resistance of wood coatings - Matjaž Pavlič; Jure Vrbec; Jure Žigon; Marko Petrič (Les)
After wood has been coated and exposed to external climatic conditions and/or elevated temperatures, staining of the coating film by hydrophilic and lipophilic extractives may occur where knots are located. For this reason, the knot staining resistance of the coating system is very important. In our study, we tested some basic types of white pigmented systems. In doing so, we adapted the method SIST EN 927-7:2020 according to our capabilities, optimized it and critically evaluated whether there is room for improvement of the standardized method. The results of our research showed that the knot staining resistance of coating systems is related to the type of solvent in the coatings, the hiding power of the system and its build-up or dry film thickness. Accordingly, solvent-borne coatings were found to be better, as were those containing more pigments and those with a higher dry film thickness. We have also found that by evaluating the colour difference on the regions with and without knots before exposure and accounting for this in evaluation of colour differences after exposure, we can make a much more objective classification of coating systems according to their effectiveness against knot staining. Based on this finding, we believe that the standardized method needs to be corrected accordingly.